THE USE OF EDMODO TO MOTIVATE STUDENTS IN WRITING - Tambunan, Christoper (2015)
Edmodo is a social-learning network that helps students, parents, administrators, and teachers collaborate about resources, assessment and content on a secure and safe learning management platform. This study utilised Edmodo to find out its effectiveness in motivating students in writing and to see the students' responses towards the use of Edmodo itself. The subjects of this study were tenth grade students at Senior High School in Bandung. This study employed two different classes, namely experimental and control group. The result showed that the experimental group had improvement of pre-test and post-test from 64.8 to 71.6. While the control group had improvement from 67.2 to 68.8. It indicates that the experimental group got the improvement higher than the control group. Based on the statistical analysis by using SPSS, data showed that experimental group had tobt 3.781 with p=0,05, df=24, and tcrit 1,71. In other words, tobt > tcrit. It indicates that there is statistically significant improvement between pre-test and post-test in experimental group. In addition, the responses of students showed that almost 80% students agreed that Edmodo is interesting, flexible, as well as able to improve critical thinking, expression, confidence, motivation and writing.